A dimensão socioambiental na educação do campo em Vitória da Conquista - BA - Costa, Glauber Barros Alves (2011)
Environmental Education (EE) is an educational process conceived in social groups, which in the 80's and 90 gained grounds in the country, still reductionist and uncritical practices. From a process of renovation and affirmation of the EE such as a new education, comes out the proposal for an EA emancipatory and transformative, that is the central object of this research. Based on the hypothesis that the conceptions and analysis of teachers working with environmental education (EE) reveal significant differences and that EE has not yet permeates the school as it should, the main goal of this research is to investigate and understand teachers' conceptions of Education in the countryside of Vitória da Conquista, who work in elementary school II, with respect to EE. The research developed in this study is characterized as an exploratory and qualitative, since the idea is to let the problem visible, to discuss it, analyze it and understand it, consistently and committed to scientific rigor. The main goal was in order to archive the main goal the collect of data and the analyses of documents was used as an instrument. The Project for Education in the countryside‟s and Response letter from the Education‟s secretariat of the city to the Judiciary regarding the development of the EE was purpose of analyzing the theoretical conceptions which they bring and how EE is presented by those documents. The others research tools are the questionnaire that served as a sample of the universe in which teachers worked with EE and from there. The interview with the teachers of the main study was to understand the concepts they have on the concern the environmental dimension in the school. These instruments were used to elicit the of views of Environmental Education, Environment, relationship EE and Education in the countryside. The Education in the countryside (EC') is implemented in rural areas of Vitoria da Conquista justifying the need to understand this education, and how EE and EC' intertwine, intersect and promote a critical and emancipatory education in the field of your teachers and students.It‟s expect as the result of this research the analysis of the reflection in the training of teachers on their conceptions and practices within the rural school environment and present data in a original study that it seeks comment and discussing on the relationship of EA with EC.